2012
DOI: 10.1136/medethics-2012-100571
|View full text |Cite
|
Sign up to set email alerts
|

Factors that facilitate or constrain the use of continuous sedation at the end of life by physicians and nurses in Belgium: results from a focus group study

Abstract: Continuous sedation at the end of life (CS) is the practice whereby a physician uses sedatives to reduce or take away a patient's consciousness until death. Although the incidence of CS is rising, as of yet little research has been conducted on how the administration of CS is experienced by medical practitioners. Existing research shows that many differences exist between medical practitioners regarding how and how often they perform CS. We conducted a focus group study to find out which factors may facilitate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
9

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 10 publications
0
10
0
9
Order By: Relevance
“…This indicates that there is a lack of a common understanding about the mechanism of how the practice of CDS is related to healthcare professionals’ emotional well-being. Raus et al [27] have shown that the emotional impact of being involved in CDS depends on different dimensions of closeness, defined as the degree to which healthcare professionals feel responsible for CDS decisions or administration [28]. Accordingly, the risk for CDS-related burden is related to professionals’ perceived closeness in CDS decisions, their emotional and physical closeness to the patient, and their perceived causal closeness [28].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This indicates that there is a lack of a common understanding about the mechanism of how the practice of CDS is related to healthcare professionals’ emotional well-being. Raus et al [27] have shown that the emotional impact of being involved in CDS depends on different dimensions of closeness, defined as the degree to which healthcare professionals feel responsible for CDS decisions or administration [28]. Accordingly, the risk for CDS-related burden is related to professionals’ perceived closeness in CDS decisions, their emotional and physical closeness to the patient, and their perceived causal closeness [28].…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that healthcare professionals’ experience with the practice of CDS is particularly positive when decisions are made in a team involving patients and the family [4750]. Recent findings have confirmed that the process of multidisciplinary decision-making aids professionals dealing with the CDS practice by reducing its emotional impact through shared responsibility [27]. As a source of emotional support an effective team approach can even protect palliative care professionals from burnout [14, 51–53].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies reported in the Journal of Medical Ethics add to the growing body of qualitative evidence relating to the use of sedatives at the end of life 1 2. Respondents in the two studies affirm a number of important concerns, most of which have been elaborated in the philosophy and palliative care literature, relating to the use of sedation.…”
mentioning
confidence: 98%
“…However, there are at least two further distinct categories of use of sedative drugs in dying patients with, naturally, some overlap between all three categories. The second category (which is the explicit focus of the paper by Raus et al 2) is continuous sedation to unconsciousness, with the aim that the patient remains unconscious until she dies. If the sedation starts early enough in the course of the patient's illness, and if nutrition and hydration are withheld, death is clearly going to be hastened.…”
mentioning
confidence: 99%